2015
DOI: 10.1136/vr.103006
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of Angiostrongylus vasorum in dogs and slugs around a new endemic focus in Scotland

Abstract: The nematode parasite Angiostrongylus vasorum is an increasingly important cause of respiratory and other diseases in dogs. Geographical spread from previously limited endemic foci has occurred rapidly. This paper investigates parasite epidemiology around the location of the first reported case in Scotland in 2009: by detection of A vasorum-specific DNA in gastropod intermediate hosts, and in dogs circulating DNA and specific antibodies, and first stage larvae in faeces. Overall prevalence in gastropods was 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…Primarily slug species were naturally infected, especially Arion spp. (rufus, lusitanus, ater, distinctus), Limax maximus and Tandonia sowerbyi (Guilhon and Bressou, 1960;Eckert and Lämmler, 1972;Ferdushy et al, 2009;Patel et al, 2014), and recently also the snail Helix aspersa was found PCR-positive for A. vasorum (Helm et al, 2015). The occurrence of these species is acknowledged also for Switzerland (with the exception of T. sowerbyi), and their natural habitat is mostly situated at altitudes from 200-1100 m asl, though they can also be found at altitudes as high as 2000 m asl (Boschi, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Primarily slug species were naturally infected, especially Arion spp. (rufus, lusitanus, ater, distinctus), Limax maximus and Tandonia sowerbyi (Guilhon and Bressou, 1960;Eckert and Lämmler, 1972;Ferdushy et al, 2009;Patel et al, 2014), and recently also the snail Helix aspersa was found PCR-positive for A. vasorum (Helm et al, 2015). The occurrence of these species is acknowledged also for Switzerland (with the exception of T. sowerbyi), and their natural habitat is mostly situated at altitudes from 200-1100 m asl, though they can also be found at altitudes as high as 2000 m asl (Boschi, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…dispersal of juvenile animals), dogs (e.g. travelling) and intermediate hosts as already discussed by others [ 13 , 14 ]. However, further studies are needed to understand the contribution of environmental factors as well as different species of intermediate and final hosts to the epidemiology of lungworm infections.…”
Section: Discussionmentioning
confidence: 99%
“…Under field conditions, the number of L1 acquired by a slug (and the number of slugs ingested by the final hosts) cannot be determined. Nevertheless, the coprophagic behaviour of some Arionidae species (Boschi 2011) together with their large size can result in higher larval burdens (Patel and others 2014), confirming their importance (Helm and others 2015). …”
mentioning
confidence: 95%
“…The first endemic case in a dog in Scotland was described in 2009 (Helm and others 2009). A study by Helm and colleagues (2015), summarised on p 46 of this issue of Veterinary Record , reports on the occurrence of A vasorum in slugs. Of the intermediate hosts collected in three defined areas around Glasgow, 6.7 per cent were positive for A vasorum DNA.…”
mentioning
confidence: 99%